73.5k views
2 votes
What’s the answer??? (SOMEONE PLEASE HELP)

What’s the answer??? (SOMEONE PLEASE HELP)-example-1
User Genevive
by
6.1k points

2 Answers

2 votes

-
(3y)/(x^(2) )

separate the factors as products


(-24)/(8) ×
(x^(4) )/(x^(6) ) ×
(y^(3) )/(y^(2) )

using the rule of exponents


(a^(m) )/(a^(n) ) =
a^((m-n)) if m > n

and
(1)/(a^((n-m)) ) if n > m

= - 3 ×
(1)/(x^((6-4)) ) ×
y^((3-2))

= - 3 ×
(1)/(x^(2) ) × y = -
(3y)/(x^(2) )



User Stephen McDaniel
by
5.4k points
1 vote


\frac{ - 24 {x}^(4){y}^(3) }{8 {x}^(6) {y}^(2) } = \frac{ - 3y}{ {x}^(2) }
User Takeisha
by
4.9k points